Cobalt‐Catalyzed Intramolecular Markovnikov Hydrocarbonylation of Unactivated Alkenes via Hydrogen Atom Transfer - Jiang, Donghao; Li, Xinzhu; Xiao, Mengdie; Cheng, Li‐Jie (Angewandte Chemie International Edition, 2024)
A cobalt‐catalyzed intramolecular Markovnikov hydroalkoxycarbonylation and hydroaminocarbonylation of unactivated alkenes has been developed, enabling highly chemo‐ and regioselective synthesis of α‐alkylated γ‐lactones and α‐alkylated γ‐lactams in good yields. The mild reaction conditions allow use of mono‐, di‐ and trisubstituted alkenes bearing a variety of functional groups. Preliminary mechanistic studies suggest the reaction proceeds through a CO‐mediated hydrogen atom transfer (HAT) and radical‐polar crossover (RPC) process, in which a cationic acylcobalt(IV) complex is proposed as the key intermediate. A cobalt‐catalyzed intramolecular Markovnikov hydroalkoxycarbonylation and hydroaminocarbonylation of unactivated alkenes has been developed, enabling highly chemo‐ and regioselective synthesis of α‐alkylated γ‐lactones as well as α‐alkylated γ‐lactams under mild reaction conditions. Mechanistic studies suggest the reaction proceeds through a CO‐mediated hydrogen atom transfer (HAT) and radical‐polar crossover (RPC) process.